The quality of Australian Indigenous primary health care research focusing on social and emotional wellbeing: a systematic review - Sara Farnbach; Anne-Maree Eades; Jamie K Fernando; Josephine D Gwynn; Nick Glozier; Maree L Hackett (Sax Institute, 2017)
Objectives and importance of the study: Primary health care research focused on Aboriginal and Torres Strait Islander (Indigenous) people is needed to ensure that key frontline services provide evidence based and culturally appropriate care. We systematically reviewed the published primary health care literature to identify research designs, processes and outcomes, and assess the scientific quality of research focused on social and emotional wellbeing. This will inform future research to improve evidence based, culturally appropriate primary health care. Study type: Systematic review in accordance with PRISMA and MOOSE guidelines. Methods: Four databases and one Indigenous-specific project website were searched for qualitative, quantitative and mixed-method published research. Studies that were conducted in primary health care services and focused on the social and emotional wellbeing of Indigenous people were included. Scientific quality was assessed using risk-of-bias assessment tools that were modified to meet our aims. We assessed community acceptance by identifying the involvement of community governance structures and representation during research development, conduct and reporting. Data were extracted using standard forms developed for this review. Results: We included 32 articles, which reported on 25 studies. Qualitative and mixed methods were used in 18 studies. Twelve articles were judged as high or unclear risk of bias, four as moderate and five as low risk of bias. Another four studies were not able to be assessed as they did not align with the risk-of-bias tools. Of the five articles judged as low risk of bias, two also had high community acceptance and both of these were qualitative. One used a phenomenological approach and the other combined participatory action research with a social-ecological perspective and incorporated 'two-way learning' principles. Of the 16 studies where a primary outcome was identified, eight aimed to identify perceptions or experiences. The remaining studies assessed resources, or evaluated services, interventions, programs or policies. We were unable to identify primary outcomes in eight studies. Conclusion: Conducting Indigenous-focused primary health care research that is scientifically robust, culturally appropriate and produces community-level outcomes is challenging. We suggest that research teams use participatory, culturally sensitive approaches and collaborate closely to plan and implement high-quality research that incorporates local perspectives. Research should result in beneficial outcomes for the communities involved.